SEJARAH DAN PERAN STRATEGIS BENTENG PENDEM CILACAP PADA MASA PENJAJAHAN BELANDA DAN JEPANG TAHUN 1879 – 1945 - Puspita Sari, Niken; Triwahana (Universitas PGRI Yogyakarta, 2024)
This study aims to (1) examine the history of the construction of Benteng Pendem Cilacap, (2) investigate the function of Benteng Pendem Cilacap during Dutch and Japanese colonial periods, and (3) analyze changes in Benteng Pendem Cilacap between 1879 and 1945. The research was conducted in Cilacap Regency, Central Java, using historical research methods. Data were collected through literature review, and the research process involved four steps: heuristic, verification, interpretation, and historiography. The findings indicate that Benteng Pendem was built by the Dutch in 1861 as part of a colonial defense strategy along the southern coast of Java. The fort served to monitor and protect the coastal area from external threats, primarily from sea attacks. In 1942, during the Japanese occupation, Benteng Pendem was taken over and repurposed as part of Japan's defense strategy in the context of World War II. During this period, the fort underwent modifications, including the addition of four bunkers on the upper level to provide protection from aerial attacks.